2014
DOI: 10.17795/ajcmi-21622
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Candiduria in Critically Ill Patients Admitted to Intensive Care Units in Qazvin, Iran

Abstract: Background: A broad variety of fungi, especially Candida species, are becoming increasingly common causes of urinary tract infections in hospital settings. Objectives: The current cross-sectional descriptive study aimed to determine the causative agents, risk factors and incidence rate of candiduria in critically ill patients, hospitalized in intensive care units (ICUs) of four Iranian hospitals. Patients and Methods: A total of 155 children and adult patients, admitted to ICUs of the four university education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Urinary catheterization increases the risk of nosocomial UTIs up to 97% [ 9 ] and the longer durations of catheter usage lead to the appearance of more infectious organisms in the urine [ 10 ]. Fungal UTIs caused by yeast, such as Candida species, have increased in hospitalized patients over the last decade, especially HF patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary catheterization increases the risk of nosocomial UTIs up to 97% [ 9 ] and the longer durations of catheter usage lead to the appearance of more infectious organisms in the urine [ 10 ]. Fungal UTIs caused by yeast, such as Candida species, have increased in hospitalized patients over the last decade, especially HF patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluconazole is an antifungal triazole drug which is used as the first line of systemic treatment in patients undergoing chemotherapy. Furthermore, fluconazole is widely used to prevent fungal infections in neutropenic patients with malignancy 21,22 . Various reports have shown that over the past few decades, the susceptibility of albicans and non‐ albicans species to fluconazole has gradually decreased 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the prevalence of candiduria is more common in female patients compared to male patients due to the reasons of anatomical and functional characteristics of the urinary system [4]. It is probably due to the shorter length of the female urethra, transmission from the female genital tract to the urinary tract, and the anti-Candida activity of prostatic fluid in males [17]. Furthermore, because the female urethra's external opening is close to the vagina and anus, which have higher levels of bacteria and yeast (i.e., approximately 75% of women will experience at least one episode of vulvovaginal candidiasis) [18], bacteria and yeast can easily enter the vagina and then enter the bladder [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those studies, a study conducted in Turkey in 2006 also showed that the risk of candiduria was increased by two folds in patients who had a history of diabetes mellitus compared to patients who did not have diabetes mellitus (P value=0.044; OR=2.002; 95% CI=1.013-3.957) [10]. Diabetic patients experience an increased threat of candiduria because they have a tendency for Candida colonization/infection through increased fungal growth in the urinary tract as a consequence of impaired phagocytic activity as a result of decreased host resistance to fungal invasion [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation